2022
DOI: 10.1007/s40519-022-01370-1
|View full text |Cite
|
Sign up to set email alerts
|

Phonological working memory is adversely affected in adults with anorexia nervosa: a systematic literature review

Abstract: Purpose Cognitive restraint has potentiating and deleterious effects on working memory (WM) in anorexia nervosa (AN). Conflicting evidence may be due to heterogeneity of tasks examining different WM components (e.g., verbal/auditory versus visuospatial), and differences in adolescent versus adult AN. Additionally, differential cognitive profiles of restricting versus binge/purging subtypes, comorbid psychiatric disorders and psychotropic medication use may confound findings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 141 publications
(352 reference statements)
0
1
0
Order By: Relevance
“…As with episodic memory, much of the research on working memory in EDs has focused on evaluating general impairments (or enhancements) of working memory (e.g., lower working memory capacity for words, digits, and other neutral stimuli, impaired ability to ignore food‐related and neutral distractors when utilizing working memory, impaired working memory updating), and the results to date have been similarly mixed (Brooks, 2016; Voon, 2015). For example, some studies suggest that individuals with restricting‐type EDs, such as AN, may have increased working memory capacity compared with individuals with binge‐spectrum EDs or controls (Brooks et al, 2012; Dahlén et al, 2022; Israel et al, 2015), though other studies have found reduced capacity in AN or no difference between groups (Fowler et al, 2006; Weider et al, 2016). Research in BED and BN has produced similarly mixed evidence for general working memory dysfunction.…”
Section: Back To the Future: Progressing Memory Research In Eating Di...mentioning
confidence: 99%
“…As with episodic memory, much of the research on working memory in EDs has focused on evaluating general impairments (or enhancements) of working memory (e.g., lower working memory capacity for words, digits, and other neutral stimuli, impaired ability to ignore food‐related and neutral distractors when utilizing working memory, impaired working memory updating), and the results to date have been similarly mixed (Brooks, 2016; Voon, 2015). For example, some studies suggest that individuals with restricting‐type EDs, such as AN, may have increased working memory capacity compared with individuals with binge‐spectrum EDs or controls (Brooks et al, 2012; Dahlén et al, 2022; Israel et al, 2015), though other studies have found reduced capacity in AN or no difference between groups (Fowler et al, 2006; Weider et al, 2016). Research in BED and BN has produced similarly mixed evidence for general working memory dysfunction.…”
Section: Back To the Future: Progressing Memory Research In Eating Di...mentioning
confidence: 99%